Is Thoracic Aortic Diameter an Independent Predictor of Cardiovascular Disease and Mortality? A Narrative Review - Tadic, Marijana; Gherbesi, Elisa; Sala, Carla; Carugo, Stefano; Cuspidi, Cesare (Frontiers in Cardiovascular Medicine, 2022)
Subclinical alterations in cardiac structure and function include a variety of abnormal phenotypes of recognized adverse prognostic value such as left ventricular hypertrophy (LVH), concentric remodelling, systolic/diastolic dysfunction, left atrial dilatation, alterations of LV geometry. The excess cardiovascular risk associated with these markers has been documented in multiple clinical settings, including the general population, hypertensive cohorts, patients with coronary heart disease, diabetes mellitus, chronic heart failure and chronic kidney disease. On the contrary, the value of aortic root (AR) and ascending aortic diameter in predicting cardiovascular outcomes and all-cause mortality in populations free from overt aortic pathology is still debated. The present review, aimed at pointing out the prognostic implications of thoracic aortic dimensions in populations free from known connective and aortic diseases, suggests that available evidence supporting an association between aortic diameter and cardiovascular events as well as all-cause mortality is based on a limited number of studies, conducted with different imaging techniques and definition of the aortic phenotype.